Plant Products as Inhibitors of Coronavirus 3CL Protease - Mandal, Anirban; Jha, Ajeet Kumar; Hazra, Banasri (Frontiers in Pharmacology, 2021)
The recent outbreak of coronavirus disease 2019 (COVID-19) has infected more than 7 million people worldwide till June 2020, claiming 0.4 million lives so far, with the numbers still going up in a few countries. The ongoing pandemic has created an alarming situation due to extensive loss of human lives and economy, posing enormous threat to global health security. Till date, there are no approved antiviral drugs or vaccines against COVID-19, although a number of clinical trials are under way to deal with the highly contagious and fatal infection. The coronaviruses encode a 3-chymotrypsin-like cysteine protease (3CLpro), also known as viral main protease (Mpro). The functional importance of this proteolytic enzyme in the viral life cycle makes 3CLpro a promising target for the development of drugs directed against SARS-CoV-2 and other coronavirus infections. To deal with the unforeseen situation, HIV protease inhibitors (lopinavir / ritonavir) are currently being used for the treatment of COVID-19 with some success. This underlines the importance of the inhibitory mechanism against 3CL protein in the design of potent anti-coronavirus drugs in the development pipeline. Plant products, since time immemorial, served as an indispensable resource for unearthing significant ‘leads’ to novel therapeutic agents. A number of traditional medicinal plants and plant-derived molecules are capable of inhibiting coronavirus 3CL protein. For example, plants like Isatis indigotica, Torreya nucifera, Psoralea corylifolia and Rheum palmatum have exhibited strong anti-3CLpro activities. Again, many phytochemicals, such as bavachinin, psoralidin, betulinic acid, curcumin, hinokinin, have shown encouraging antiviral activity, and might play promising roles in discovering drugs against COVID-19 in future. The present review will focus on plant-derived 3CLpro inhibitors and their proposed mechanism of action, as well as highlight some of the prospective plant constituents waiting to be evaluated against this protease enzyme.